Maternal and paternal quality of life in children with epilepsy: Who is affected more? - Koc, Guray; Bek, Semai; Vurucu, Sebahattin; Gokcil, Zeki; Odabasi, Zeki (Academic Press Inc Elsevier Science, 2019)
Introduction: This study aimed to evaluate and compare parental quality of life (QoL), anxiety, and depression in mothers and fathers of children with epilepsy (CWE). Material and methods: Thirty-three mothers and 33 fathers of 33 CWE (aged 1-16 years) completed the World Health Organization Quality of Life-Brief Form (WHOQOL-BREF), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) questionnaires. Scores for the questionnaires were compared for 36 mothers and 36 fathers of 36 healthy children (aged 1-16 years). The control group consisted of hospital staff who had healthy children. Results: Mothers of CWE had significantly lower scores for the environmental domain of the WHOQOL-BREF, BDI, and BAI questionnaires compared with mothers of healthy children (p < 0.05), while fathers showed no significant difference (p > 0.05). Furthermore, mothers of CWE had significantly lower scores for the psychological domain of the WHOQOL-BREF compared with fathers (p < 0.05). The environmental domain of the WHOQOL-BREF questionnaire was negatively correlated with the number of children for all parents (r = -0.342, p = 0.005), and the BAI and BDI scales were positively correlated with the number of children (r = 0.386, p = 0.001; r = 0.395, p = 0.001, respectively). Conclusion: Mothers of CWE showed lower scores for the psychological domain in QoL analysis compared with fathers of CWE, as well as decreased emotional wellbeing and lower QoL compared with mothers of healthy children. These results reveal that parents of CWE with a larger family size are more affected and that mothers of CWE are more affected. The reasons for these findings and possible interventions that might improve QoL, particularly in mothers with CWE, require further research. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Parents; Quality of life; Depression; Anxiety